DESIGNING GOODS SUPPLY AND MARKETING INFORMATION SYSTEM THROUGH SCRUM AGILE DEVELOPMENT METHOD IN MELODI MEGA KENCANA LTD. - Melda Agarina; Sri Karnila; Arman Suryadi Karim; Zulkarnaini Zulkarnaini (Proceeding International Conference on Information Technology and Business, 2020)
Melodi Mega Kencana Ltd. was the business entity engaged in the field of selling daily needs through the sales process such as buying dozens or score of goods and selling goods in a small quantity. Melodi Mega Kencana Ltd., currently already had several consumers. Melodi Mega Kencana Ltd., still used conventional way for the marketing processes and recording stock items. This became the problems occurred repeatedly in Melodi Mega Kencana ltd. e.g., 1) a incompatibility between number of incoming goods, outgoing goods, and available stock items; 2) the difficulties in making good reports sales and inventory reports in the beginning of the week and in the end of each month. The objective of this study was designing the goods supply and marketing information system in Mega Kencana Melody Ltd. The method of this study was the scrum agile development method to create a good system in accordance with the users' wishes. The Scrum method had a flexible, evolutionary framework, and reliable in solving complex adaptive problems and generated creativity and productivity from software design. With this system, it was expected to facilitate the Melodi Mega Kencana Ltd., in the process of marketing products to customers and improve the process of making reports and managing stock items so that there were no repeated errors in changing the number of goods with the number of incoming and outgoing goods.Keywords: Scrum, Marketing, stock of goods